Effect of temperature, viscosity and surface tension on gelatine structures produced by modified 3D printer - (:unkn) unknown (IOP PUBLISHING LTD, 2017)
In the present study, gelatine scaffolds were manufactured by using modified 3D (3 Dimensional) printing machine and the effect of different parameters on scaffold structure were investigated. Such as; temperature, viscosity and surface tension of the gelatine solutions. The varying of gelatine solutions (1, 3, 5, 10, 15 and 20 wt.%) were prepared and characterized. It has been detected that, viscosity of those solutions were highly influenced by temperature and gelatine concentration. Specific CAD (Computer Assistant Design) model which has 67% porosity and original design were created via computer software. However, at high temperatures gelatine solutions caused like liquid but at the lower temperatures were observed the opposite behaviour. In addition to that, viscosity of 1,3,5 wt.% solutions were not enough to build a structure and 20 wt.% gelatine solution too hard to handle, because of the sudden viscosity changes with temperature. Even though, scaffold of the 20 wt.% gelatine solution printed hardly but it was observed the best printed solutions, which were 10 and 15 wt.% gelatine solutions. As a result, 3D printing of gelatine were found the values of the best temperature, viscosity, surface tension and gelatine concentration such as 25-35 degrees C, 36-163 cP, 46-59 mN/m and 15 wt.% gelatine concentration respectively.
Keywords: FABRICATION; SCAFFOLDS